Developing a CFD methodology for the analysis of flow stability in heated channels with fluids at supercritical pressures - Ampomah-Amoako, E.; Ambrosin, W. (Annals of Nuclear Energy, 2013)
The paper presents the first results of a systematic methodology aimed at assessing the feasibility of analyses by CFD codes of flow instabilities in heated channels containing supercritical fluids. The research makes use of features presently available in CFD models, in the aim to move step-by-step from simple channel cases towards the analysis of more realistic fuel bundle subchannels. In the present step, basing on previous experience, the STAR-CCM+ code is adopted to solve flow stability problems in circular channels and fuel bundle slices without heating structures, in the aim to characterise the response of CFD models in the analysis of purely thermal-hydraulic instability phenomena. Some of the effects related to numerical discretisation, flow direction with respect to gravity and fluid properties are studied, comparing the stability thresholds identified by transient calculations with maps set up by in-house 1D codes developed and adopted in previous work. Both static and dynamic instabilities are observed, clearly showing the contiguity of these two kinds of phenomena as a function of inlet fluid subcooling. Conclusions are finally drawn about the promising features of CFD codes for such applications, sketching the lines of the work already going on in order to address more realistic reactor scale conditions. © 2012 Elsevier B.V. All rights reserved.
Keywords: CFD; Fluid-to-fluid comparison; Numerical discretisation; Stability; Supercritical pressure